Multiple sclerosis-induced reduction in the yield of a mouse cell line. - Carp, R I (1975)
Cultures of a mouse cell line (PAM) were treated with 71 multiple sclerosis (MS) and 45 non-MS samples. Of the cultures treated with MS material, 80 percent (58) showed a reduction in cell yield (compared to untreated controls) of at least 20 percent by the third passage after inoculation. The MS samples were from 40 MS cases, and a total of 36 cases yielded at least one positive sample. The agent responsible for the decrease was not limited to nervous tissue, but was also found in serum, cerebrospinal fluid, spleen, kidney, and lymph node of MS patients. Positive samples were present at every stage of the disease. None of the non-MS samples yielded cell counts significantly different from untreated controls. The non-MS category included 12 samples from healthy individuals, 13 assorted non-central nervous system disease samples, and the following central nervous system disease samples: six subacute sclerosing panencephalitis, three Huntington's chorea, two Parkinsonism, six amyotrophic lateral sclerosis, one stroke, one encephalopathy, and one epilepsy. Brain homogenates from mice inoculated with MS tissues elicited the decrease, whereas brain homogenates from mice inoculated with non-MS samples did not.